Supporting Young People’s Mental Health: Reconceptualizing the Role of Schools or a Step Too far? - Glazzard, Jonathan; Stones, Samuel (Frontiers in Education, 2021)
This article provides an overview of the UK government’s strategy for children’s mental health. Critique of the mental health policy document demonstrates the adoption of a clinical approach to resolving the mental health ‘crisis’. We argue that a clinical solution is not based on robust evidence and that the policy reflects a medical model which positions children and young people with mental ill health through a deficit lens. We argue that the government should, instead, adopt a systemic response directly addressing the underlying factors which cause mental ill health. We argue that a clinical response at the level of the individual is not appropriate for most children and young people with mental ill health and that there needs to be an urgent review of policy.